Bond strength of milled and printed zirconia to 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP) resin cement as a function of ceramic conditioning, disinfection and ageing - Bömicke, Wolfgang; Schwindling, Franz Sebastian; Rammelsberg, Peter; Rues, Stefan (Materials, 2024)
This study aimed to assess the suitability of printed zirconia (ZrO2) for adhesive cementation compared to milled ZrO2. Surface conditioning protocols and disinfection effects on bond strength were also investigated. ZrO2 discs (n = 14/group) underwent either alumina (Al2O3) airborne particle abrasion (APA; 50 µm, 0.10 MPa) or tribochemical silicatisation (TSC; 110 µm Al2O3, 0.28 MPa and 110 µm silica-modified Al2O3, 0.28 MPa), followed by disinfection (1 min immersion in 70% isopropanol, 15 s water spray, 10 s drying with oil-free air) for half of the discs. A resin cement containing 10-methacryloyloxydecyl dihydrogen phosphate (10-MDP) was used for bonding (for TSC specimens after application of a primer containing silane and 10-MDP). Tensile bond strength was measured after storage for 24 h at 100% relative humidity or after 30 days in water, including 7500 thermocycles. Surface conditioning significantly affected bond strength, with higher values for TSC specimens. Ageing and the interaction of conditioning, disinfection and ageing also impacted bond strength. Disinfection combined with APA mitigated ageing-related bond strength decrease but exacerbated it for TSC specimens. Despite these effects, high bond strengths were maintained even after disinfection and ageing. Adhesive cementation of printed ZrO2 restorations exhibited comparable bond strengths to milled ZrO2, highlighting its feasibility in clinical applications.